Does Knowledge Based Psychological Ownership Matter? Transformational Leadership and Knowledge Hiding: A Proposed Framework - Sahnun, Ladan; Nordin, Norani; Belal, H. M. (Centre of Business & Economic Research, 2017)
The prevalent and negative impact of knowledge hiding behaviour among employees has called the attention of both practitioners and researchers to begin investigations on its causes, and other factors that influence it on both the targets and perpetrators. Some of the possible suggested antecedents of knowledge hiding studied include trust, job characteristic, organisational culture, and workplace environment. Despite these studies, few have attempted to investigate the influence of leadership, particularly, transformational leadership on knowledge hiding. Previous studies also indicated conflicting results, and the mechanisms through which transformational leadership influences knowledge hiding are not adequately addressed. Therefore, mediator variable is suggested. Hence, this paper proposes knowledge psychological ownership as a potential mediator on the relationship between transformational leadership and knowledge hiding behaviour of an employee in the organization. We hereby argue that transformational leadership through knowledge psychological ownership will influence employees to refrain from the knowledge hiding behaviour that may negatively affect the organisation and encourage knowledge sharing to improve the performance of the organization